2020
DOI: 10.1111/cts.12840
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of Remdesivir, An Antiviral for Treatment of COVID‐19, in Healthy Subjects

Abstract: Remdesivir (RDV), a single diastereomeric monophosphoramidate prodrug that inhibits viral RNA polymerases, has potent in vitro antiviral activity against severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). RDV received the US Food and Drug Administration (FDA)’s emergency use authorization in the United States and approval in Japan for treatment of patients with severe coronavirus disease 2019 (COVID‐19). This report describes two phase I studies that evaluated the safety and pharmacokinetics (PKs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
337
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(361 citation statements)
references
References 25 publications
(30 reference statements)
16
337
2
6
Order By: Relevance
“…Many pitfalls still exist with understanding COVID-19 and the use of remdesivir. Optimum time of administration in relation of the benefit of remdesivir for COVID-19 has yet to be clear, although initiation is generally considered once oxygen saturations drop below 94% [1,2,8,14]. Both of our patients developed sinus bradycardia within 20-40 minutes of infusion time (at drug peaks), and typically doses are infused over a full hour to completion [8].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many pitfalls still exist with understanding COVID-19 and the use of remdesivir. Optimum time of administration in relation of the benefit of remdesivir for COVID-19 has yet to be clear, although initiation is generally considered once oxygen saturations drop below 94% [1,2,8,14]. Both of our patients developed sinus bradycardia within 20-40 minutes of infusion time (at drug peaks), and typically doses are infused over a full hour to completion [8].…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that it contributed to the prolongation of the QT interval in this patient despite having been discontinued shortly before remdesivir initiation. Remdesivir itself has been mentioned in its own right to have an effect on the QT interval, but more studies are needed to support a causality [8,10,12]. Cardiac disturbances in COVID-19 patients receiving remdesivir seem to be primarily due to bradycardia or hypotension in the studies found and less commonly being due to QT prolongation [4,5,10,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a consideration of free drug concentrations in other relevant matrices is likely to be needed to underpin successful therapeutic development, but a lack of standardised methodology complicated robust investigation. Figure 1B shows the mean plasma concentration time profile for remdesivir following multiple dose administration of 150mg to healthy volunteers (30). The free drug fraction of remdesivir in human plasma has been reported as 0.121 (12.1%) (31) and this value has been used to derive the unbound plasma profile, which is also shown in Figure 1B.…”
Section: Accepted Articlementioning
confidence: 96%
“…With respect to drug development, it is anti-viral drugs, especially those which are known from former endeavours to fight against human immunodeficiency virus or other viral infections, targeting replication-crucial proteins to interfere with viral replication such as protease inhibitors, reverse transcriptase or endonuclease inhibitors [ 1 , 2 ]. An inhibitor of the RNA dependent RNA polymerase, Remdesivir [ 3 ], which was originally under development for the combat of Ebola has already been approved for its use in COVID-19.…”
Section: Introductionmentioning
confidence: 99%